PHRASEOLOGICAL UNITS AND THEIR ASSOCIATIVE PROPERTIES REPRESENTING HUMAN CHARACTER (Scientific journal of the Fergana State University, 2025)
This article explores the associative properties of phraseological units used to express character in literature. Phraseological units, which include idioms, metaphors, similes and other figurative expressions, often carry complex webs of meaning and connotation beyond their literal semantic content. Through both qualitative analysis of selected phraseological units and quantitative corpus analysis, this study demonstrates that the associative meanings of phraseological units related to character tend to cluster around particular semantic fields and reflect cultural views and stereotypes about personality traits and types. An awareness of these associative meanings is important for both literary analysis and cross-cultural communication. Further research is needed on the associative properties of phraseological units in other semantic domains beyond character and personality.